A novel cell design of vanadium redox flow batteries for enhancing energy and power performance. (15th July 2018) - Al-Yasiri, Mohammed; Park, Jonghyun
Highlights: A new structure for vanadium redox flow batteries is developed. Embedded serpentine flow channels eliminate end plates and gaskets. The new structure improves safety and cell life, and reduces the assembly cost. Abstract: The Vanadium Redox Flow Battery (VRFB) is one of the most promising electrochemical energy storage systems considered to be suitable for a wide range of renewable energy applications. In this work, a novel cell structure is designed for VRFB, which includes embedded serpentine flow channels in a non-porous and non-brittle case. This new design eliminates end plates and gaskets to improve safety, extend life, and promote ease of assembly with fewer components than traditional VRFB cells. In particular, a key challenge of conventional graphite flow field plates in which solution penetration can occur due to an easily broken and porous structure is solved by using rigid impermeable polyvinyl chloride (PVC) sheets with flow channels embedded in the sheets. Various tests, such as cycling and polarization measurements of a wide range of current and flow rates, and Electrochemical Impedance Spectroscopy (EIS) for internal resistance analysis, are performed to compare new and traditional designs. The results show that the new design keeps cycling performance stable, with better stability and energy efficiency, than conventional VRFB cells do. High power performance is also observed for the same external cell size. In addition, an abrupt potential drop caused by high contact resistance between the current collector and a porous electrode is solved by introducing a layer of the patterned graphite sheet to improve contact and electronic conductivity and, also, to function as a flow channel. Finally, an economic analysis shows that the new design not only improves battery performance, but also lowers assembly costs and facilitates assembly.